Indicators representing the level of provision of transport services and infrastructure of the region - Tursunov Ozodbek Badalovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
In the article, the indicators representing the level of provision of transport services and infrastructure of the region in the field of transport services management in Uzbekistan in recent years have been researched. In the course of the research, scientific proposals were made for the development of a system of indicators representing the level of transportation infrastructure of the region and their evaluation.